The relation between health care team and the family of dying child - Muñoz Salinas, Mara (Acta Bioethica, 2011)
The present study is a review based on bibliographic search, interviews and the experience of the author about health care process, as it is currently done, for parents that face the death of their child. This research belongs to the qualita- tive paradigm, using a semi structure interview as method of data recollection. Several answers were obtained seeing parents perception about health care of health team, mainly of nursing professionals, from diagnosis to the moment of mourning they are.